Comparison of CD4+ and CD8+ T- lymphocyte in Helicobacter pylori-negative functional dyspepsia - Leila Vahedi; Sousan Mirnajd Gerami; Kourosh Masnadi-Shirazi; Seyed Kazem Mirinezhad; Shabnam Salehi; Monireh Halimi (Babol University of Medical Sciences, 2020)
Background: Functional dyspepsia (FD) is the most common gastrointestinal disorder with several symptoms such as stomach pain and abdominal bloating. The aim of this study was to investigate and compare CD4+ and CD8+ in the Helicobacter pylori-negative functional dyspepsia and control groups. Methods: Sixty one patients (35 patients with stomach pain and 26 with abdominal bloating), and 30 controls were reviewed based on the quantity of CD4+ and CD8+ T-cells isolated from gastric mucosa biopsy samples. The comparison between variables was analyzed with a chi-square or Fisher's exact test and logistic regression analyses. P<0.05 and odds ratio (OR) with a 95% confidence interval demonstrated statistical significance. Results: A significant difference was observed between two-group patients and control group based on CD4+ and CD8+ presence, respectively (P=0.003, P=0.008). Furthermore, there was a significant difference between stomach pain-patients and control group with regard to CD4 count (P=0.01) and between abdominal bloating-patients and control group with regard to CD8 count (P=0.002). There was a decrease in both CD4+ and CD8+ T-cells in gastric mucosa in patients with FD with a significant reduction in the stomach pain-patients and abdominal bloating-patients in the number of CD4+ and CD8+ T-cells, respectively. Conclusion: These results indicated that the role of immunology in the absence of the CD4+ and CD8+ T-cells in the gastric mucosa may have a protective role against FD.